Performance prediction and athlete categorization using the anaerobic power reserve framework in rowing - Rappelt, L.; Donath, L.; Wiedemann, T.; Micke, F.; Mühlenhoff, S.; Held, S. (Medicine & Science in Sports & Exercise, 2026)
Abstract Purpose: With the Olympic rowing distance reduced to 1500 m for 2028, the anaerobic power reserve framework has been proposed to evaluate anaerobic performance and differentiate physiological profiles. This study investigated performance predictions and athlete profiles using the anaerobic power reserve framework and related physical performance measures.